2014
DOI: 10.5951/jresematheduc.45.1.0019
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles and Affordances for Integer Reasoning: An Analysis of Children's Thinking and the History of Mathematics

Abstract: We identify and document 3 cognitive obstacles, 3 cognitive affordances, and 1 type of integer understanding that can function as either an obstacle or affordance for learners while they extend their numeric domains from whole numbers to include negative integers. In particular, we highlight 2 key subsets of integer reasoning: understanding or knowledge that may, initially, interfere with one's learning integers (which we call cognitive obstacles) and understanding or knowledge that may afford progress in unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 48 publications
1
45
0
1
Order By: Relevance
“…Noticing the complicated nature of integers and contexts, we turned our attention to the literature on student thinking about integers. This literature (e.g., Bishop, Lamb, Philipp, Whitacre, Schappelle, & Lewis, 2014;Bishop, Lamb, Philipp, Whitacre, & Schappelle, 2016;Bofferding, 2014) has demonstrated that students are capable of robust reasoning about integers, but is mostly situated in how students make sense of integers in symbolic settings (e.g., how they solve problems like -2 --5 = ☐) or pre-determined contexts.…”
Section: Even the Authors Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…Noticing the complicated nature of integers and contexts, we turned our attention to the literature on student thinking about integers. This literature (e.g., Bishop, Lamb, Philipp, Whitacre, Schappelle, & Lewis, 2014;Bishop, Lamb, Philipp, Whitacre, & Schappelle, 2016;Bofferding, 2014) has demonstrated that students are capable of robust reasoning about integers, but is mostly situated in how students make sense of integers in symbolic settings (e.g., how they solve problems like -2 --5 = ☐) or pre-determined contexts.…”
Section: Even the Authors Of Thementioning
confidence: 99%
“…They may pose unrealistic stories (Mukhopadhyay, 1997) and change the structure of the number sentences (Rowell & Norwood, 1999). When working with integer operations in contexts, students may not think about the integers as adults do (e.g., Bishop, Lamb, Philipp, Whitacre, Schappelle, & Lewis, 2014;Bishop et al, 2016;Bofferding, 2014). Students may be unable to transfer integer understanding in one context to another context (Mukhopadyhyay et al, 1990).…”
Section: Challenges Of Thinking About Integers Within Contextsmentioning
confidence: 99%
“…Tidak hanya bilangan bulat positif, siswa juga mengalami kesulitan dalam memahami bilangan bulat negatif. Ketika siswa diminta untuk membandingkan bilangan tersebut, banyak diantara siswa yang menjawab salah (Bishop, Lamb, Philipp, Whitacre, Schappelle, et al, 2014;. Kemampuan bernalar siswa dapat diketahi melalui pengerjaan soal-soal, terutama soal yang membutuhkan alasan logis.…”
Section: Pendahuluanunclassified
“…In this vein, researchers also recognize the importance of students' perceptions of the feedback they receive as a way to glimpse the teacher's point of view (Bansilal, James, & Naidoo, 2009). Because how students view feedback is critical to their learning, much emphasis has been placed on the quality of teachers' feedback (Sadler, 1998) as well as a way for them to understand the state of each student's knowledge by employing strategies to elicit student understanding and methods to interpret students' products (Bishop et al, 2014;Leatham et al, 2015). Thus, formative assessment feedback is related to the effectiveness of teachers' questioning and more generally to the teacher's role as a facilitator of learning, which depends on his/her ability to observe students' learning and attend to their thinking (Lee, 2018;Lee & Cross Francis, 2018;Peterson & Leatham, 2009;Stockero, Rupnow, & Pascoe, 2015).…”
Section: Formative Assessment Practicementioning
confidence: 99%